Development and characterization of chronomodulated drug delivery system of captopril - Patil, Archana S; Dandagi, Panchaxari M; Masthiholimath, Vinayak S; Gadad, Anand P; Najwade, Basavaraj K (International Journal of Pharmaceutical Investigation)
Background: Hypertension shows circadian rhythm that there is a rise in pressure from the time of waking or before (about 4 to 8 a.m.), in most people. Conventional drug delivery system of captopril is inappropriate for the delivery of drug, as they cannot be administered just before the symptoms are worsened, because during this time the patients are asleep, bedtime dosing of captopril will not provide a therapeutic plasma drug concentration at the early hours of morning because of poor pharmacokinetic profile and shorter half-life of 1.9 hours. Thus, this study attempts to design and evaluate a chronomodulated pulsatile drug delivery system of captopril which was aimed to release the drug after a lag time of 6 hours. Materials and Methods: Present delivery system was prepared by rupturable coating method. The core containing captopril as a bioactive compound were prepared by direct compression method and then coated sequentially with an inner swelling layer containing hydrocolloid HPMC E5 and an outer rupturable layer consisted of Eudragit RL/RS (1 : 1). Total 12 formulations with different levels of inner swelling layer and outer polymeric layer were prepared and subjected to various processing and formulative parameters like the effect of core composition, level of swelling layer, and rupturable coating on lag time was investigated. In vitro drug release and rupture tests were performed using United States Pharmacopoeia paddle method at 50 rpm in 0.1N HCl and phosphate buffer of pH 6.8. Results: The results showed that as the amount of inner swelling layer increases, the lag time decreases and as the Eudragit coating level increases, the lag time increases and percent water uptake of time-dependent pulsatile release system decreases. The presence of an osmotic agent and effervescent agent helped in shortening of lag time. Conclusion: The system was found to be satisfactory in terms of release of the drug after the lag time of 6 hours.
Keywords: Captopril; circadian rhythm; rupturable layer; swelling layer; time-dependent pulsed release system